Intergovernmental Grants as Signals and the Alignment Effect: Theory and Evidence - Emanuele Bracco; Benjamin Lockwood; Francesco Porcelli; Michela Redoano (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper provides a simple political agency model to explain the effect of political alignment between different tiers of government on intergovernmental grants and election outcomes. Key features of the model are: (i) rational voters interpret public good provision as a signal of incumbent competence, and (ii) realistically, grants are unobservable to voters. In this setting, the national government will use the grant as an instrument to manipulate the public good signal for the benefit of aligned local incumbents and challengers. Then, aligned municipalities receive more grants, with this effect being stronger before elections, and the probability that the aligned local incumbent is re-elected is higher. These predictions are tested using a regression discontinuity design on a new data-set on Italian municipalities. At a second empirical stage, the national grant to municipalities is instrumented with an alignment indicator, allowing estimation of a flypaper effect for Italian municipalities.
Keywords: H20; H77; H87; D70; 330; fiscal federalism; political competition; accountability; flypaper effect